Economic and Structural Impacts of Engineered Mix Designs Over VolumetricConcrete Practice in Kathmandu Valley - Khadka, Thaman Bahadur; Khadka, Sunil; Bhomi, Sarun; Sharma, Ashish (Tribhuvan University Journal, 2026)
Nominal 1:2:3 volumetric proportioning is dominant in producing M20 concrete in the Kathmandu valley, often without any proper quality control measures. In the research, a survey was carried out at 19 construction sites, showing 72.72% of M20 sites using a 1:2:3 proportion and only 27.27% conduct laboratory-based cube tests. The structural and economic implications of this practice were evaluated through a laboratory experiment comparing representative field mixes with IS code-design mixes across two aggregate combinations: Trishuli sand with Melamchi gravel (Set 1), and both aggregates from Dhading (Set 2). Four design mixes with varying water-cement (w/c) ratios and one field-representative mix were tested per set. Results indicate that field mixes failed the IS 456 mean strength criterion (>23.5 MPa), though individual samples exceeded the 17 MPa characteristic limit. Likewise, the mixes of w/c 0.55 failed acceptance criteria in either of the two tests conducted. Within a narrow range of costs of NRs 13,240-13,950 per cubic meter of concrete, the compressive strength of the specimens ranged between 17.9 MPa and 36.4 MPa, showing substantial optimization potential without significant increase in expenses. Also, Dhading aggregates produced superior concrete than the Trishuli-Melamchi aggregates at a lower cost, attributed to better grading (Zone I vs Zone IV) and better coarse aggregates (LA abrasion:33.2% versus 36.7%; impact value: 22.6% versus 23.0%). The study concludes that standardized mix design practice, routine testing for M20, and rigorous water-cement ratio control are essential preconditions for structurally reliable concrete production in Kathmandu Valley.